SPECIALISED LEARNER CORPUS RESEARCH: A REVIEW FOR FUTURE DIRECTIONS OF THE GLOBAL AND MALAYSIAN CONTEXTS - Subramaniam, Radika; Kaur, Sheena (TEFLIN Journal, 2023)
Literature survey concerning the Learner Corpus Research (LCR) in the last 20 years has shown a paucity of studies involving specialised/discipline-specific text. Since the use of discipline-specific academic writing learner corpora is useful in determining the language pattern within the English for Specific Academic Purposes (ESAP) context, this paper presents a review of specialised LCR based on journal articles from the Web of Science database and the Google scholar, reference books and relevant websites to address the gap both globally and within the Malaysian context for future needs. The review suggests the need for more specialised/genre-specific or discipline-based learner corpus studies employing the non-native novice versus native novice and expert comparative method in both global and Malaysian contexts, with more studies executed in relation to specialised learner corpora in the latter. In relation to linguistic aspect, the understanding of lexical bundles’ communicative function can be attempted through the analysis from the core word to the surrounding pattern or discourse. The use of learner corpus as a pedagogical instrument needs also to be well-accepted and executed to enhance the teaching and learning of academic writing in ESAP classrooms via Data-Driven Learning approach or corpus-related activities.